Hubungan Perilaku Self Management Dengan Kadar Gula Darah Pada Pasien Diabetes Melitus Tipe II Di Puskesmas Sekupang Kota Batam - Rizki Sari Utami Muchtar; Siska Natalia; Wulan Minanda (Akademi Analis Kesehatan Pekalongan, 2023)
Diabetes mellitus is a chronic disease but can be controlled or prevented with self-management. Self-management of diabetes aims to control blood glucose levels optimally and prevent complications that arise. Activities that can be done include diet, physical activity/exercise, blood glucose control, taking medication regularly and foot care. This research aims to determine the relationship between self-management behavior and blood sugar levels in type 2 diabetes mellitus patients. This type of research is a quantitative research method with a correlative descriptive design with a cross sectional approach. Data collection used a non-probability sampling technique in the form of accidental sampling with a sample size of 36 respondents, using the chi square test. Most respondents have sufficient self-management (69.4%). Apart from that, the majority of respondents had normal blood sugar levels (97.2%). The results of the analysis test were obtained with a P value = 0.004 (<0.05). It is hoped that the UPTD BLUD Sekupang Community Health Center will create a diabetes self care management program with efforts to improve blood sugar control.